1986
DOI: 10.1002/1097-0142(19861201)58:11<2417::aid-cncr2820581111>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma in two brothers. An immunochemical and immunogenetic familial study

Abstract: When multiple myeloma was diagnosed within 6 months in two brothers a family study was carried out in 34 relatives to assess the genetic factors involved. The monoclonal immunoglobulin isotype identified was identical for the two brothers (IgG kappa) as well as their genotype (a = A2B12BfSDR4 GIo2/d:A9B27BfSDR2GIol). Blood protein electrophoresis and the major histocompatibility complex markers (HLA A, B, DR, Bf, glyoxalase phenotypes) were also determined in the other family members. The immunochemical study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…It has been suggested that in Waldenstrom's macroglobulinaemia there is an autosomal dominant mode of transmission linked to the HLA A2 B8 DR3 haplotype (Reiner et al, 1989), although other familial reports of this disease have failed to show a common haplotype. Grosbois et al (1986) described two brothers with multiple myeloma who had identical HLA Comparison of age at diagnosis of malignant plasma cell dyscrasia between the observed cases and those in the general population. A significant difference is observed between the age at diagnosis in the child generation (P < 0·005), but not between that of the parent generation and cases in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that in Waldenstrom's macroglobulinaemia there is an autosomal dominant mode of transmission linked to the HLA A2 B8 DR3 haplotype (Reiner et al, 1989), although other familial reports of this disease have failed to show a common haplotype. Grosbois et al (1986) described two brothers with multiple myeloma who had identical HLA Comparison of age at diagnosis of malignant plasma cell dyscrasia between the observed cases and those in the general population. A significant difference is observed between the age at diagnosis in the child generation (P < 0·005), but not between that of the parent generation and cases in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the Cw2 allele, or a gene located in proximity to this locus, may confer susceptibility to the development of MM [11]. Reports of plasma and lymphocyte dyscrasias in siblings and other near relatives of MM patients suggest that the predisposition to the development of MM may be inherited [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In only one series has a significant increase of CW5 in black Americans been demonstrated (Leech & Bryan, 1983). In familial multiple myeloma we have described previously (Grosbois et al , 1986) an HLA identity in two brothers. Loth & Perrotta (1991) also reported HLA identity in two sisters.…”
Section: Discussionmentioning
confidence: 94%
“…Multiple myeloma in two members of the same family is a rare occurrence. In a previous report we described two cases with immunochemical and immunogenetic identity and emphasized the great value of such cases for improved understanding of the disease pathogenesis (Grosbois et al , 1986).…”
mentioning
confidence: 93%